Comparison of an automated digital cell morphology analysis system with manual counting - Juan Jiao; Xin Yin; Jiali Ma; Yinglong Xia; Jianxia Xu; Shaozhe Zhao; Jie Liu (iLabmed)
Abstract Background Bionovation's CSFA800 is a new automated digital cell imaging analyzer. We evaluated the performance of the CSFA800 by comparing it with artificial peripheral blood white blood cell counting. Methods According to inclusion and exclusion criteria, 131 randomly selected samples (77 abnormal samples and 54 normal samples) were compared. Correlations between automated and manual counting results were analyzed. Manual counting was carried out according to the guidelines of the Association of Clinical and Laboratory Standards. Results Counts of neutrophils, lymphocytes, monocytes, eosinophils, basophils, and immature granulocytes obtained from CSFA800 and artificial methods were linearly and positively correlated, with R values of 0.73, 0.65, 0.24, 0.2, 0.4, and 0.63, respectively, all p < 0.05. Therefore, correlations between CSFA800 and manual counting are acceptable. Compared with the DI‐60 Automated Digital Cell Morphology System (DI‐60; Sysmex), CSFA800 is more efficient and can analyze 20,000 cells in 1 min. However, the overall accuracy of CSFA800 is not as good as DI‐60, although its counting performance is better for basophils. Conclusions The performance of CSFA800 for WBC counts is acceptable, and it displayed good performance for neutrophils, lymphocytes, and immature granulocytes. Compared to DI‐60, CSFA800 is more efficient but has slightly lower overall accuracy. To some extent, CSFA800 is helpful to optimize the clinical laboratory workflow and improve the working efficiency of inspectors.